2022
DOI: 10.1371/journal.pone.0272042
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and steroid use increase the risk of rhino-orbito-cerebral mucormycosis regardless of COVID-19 hospitalization: Case-control study, India

Abstract: Background In the ongoing COVID-19 pandemic, an increased incidence of ROCM was noted in India among those infected with COVID. We determined risk factors for rhino-orbito-cerebral mucormycosis (ROCM) post Coronavirus disease 2019 (COVID-19) among those never and ever hospitalized for COVID-19 separately through a multicentric, hospital-based, unmatched case-control study across India. Methods We defined cases and controls as those with and without post-COVID ROCM, respectively. We compared their socio-demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…Diabetes mellitus and glucocorticoid therapy were shown to be the major contributors for CAM in the case–control studies and large case series ( 2 , 3 , 6 , 21 , 35 , 37 ). Further, in addition to zinc and elevated inflammatory markers (C-reactive protein), which were also associated with CAM in this study, the use of cloth masks, nasal washing during COVID-19, and elevated serum glucose-regulated protein 78 were other possible associations described in smaller case–control studies ( 29 , 30 , 33 ). In our study, mean glycated hemoglobin values were significantly higher in the CAM cases.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Diabetes mellitus and glucocorticoid therapy were shown to be the major contributors for CAM in the case–control studies and large case series ( 2 , 3 , 6 , 21 , 35 , 37 ). Further, in addition to zinc and elevated inflammatory markers (C-reactive protein), which were also associated with CAM in this study, the use of cloth masks, nasal washing during COVID-19, and elevated serum glucose-regulated protein 78 were other possible associations described in smaller case–control studies ( 29 , 30 , 33 ). In our study, mean glycated hemoglobin values were significantly higher in the CAM cases.…”
Section: Discussionsupporting
confidence: 58%
“…However, a recent experimental aeromycological study found no evidence for this theory (25). Several case-control studies (n = 13) have assessed the risk factors associated with CAM (Appendix Table 8) (6,7,20,21,(28)(29)(30)(31)(32)(33)(34)(35)(36). In 8 studies (sample sizes ranging from 46 to 870), risk factors for CAM were assessed using multivariate analysis (6,7,(29)(30)(31)(32)(33)35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more common in patients with prior severe COVID-19, CAM cases were seen even in patients with mild COVID-19, consistent with prior reports. 16,17 The overuse of GCS, even in non-hypoxemic patients, was suggested by the fact that 80% of our CAM cohort received GCS, while only 60% of patients required supplemental oxygen. Several studies from India and elsewhere, have documented the inappropriately frequent use of GCS, even at high doses, in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…In the study conducted by Ponnaiah et al, it was shown that the use of steroids and diabetes were risk factors for the onset of CAM, with diabetic patients having a 5-times higher risk of developing CAM and those receiving steroid treatment having a 3-times higher risk [ 14 ]. In our case, the patient received steroid treatment and also had a high glycemic level, including diabetic acidosis.…”
Section: Discussionmentioning
confidence: 99%